Aplikasi Standar Proses Keperawatan: Diagnosis, Outcome, dan Intervensi pada Asuhan Keperawatan - Dheni Koerniawan; Novita Elisabeth Daeli; Srimiyati Srimiyati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to look at the quality of nursing care documentation at Myria Hospital Palembang. Analytic surveys are used to obtain an overview of nursing documentation as secondary data. Nursing care documents used were 105 documents by cluster sampling and measured using Q-DIO instruments, and analyzed descriptively. The results showed most of the medium quality in all dimensions, namely diagnosis as a process of 70 documents (67%), diagnosis as a product as many as 56 documents (53%), intervention as many as 66 documents (63%), and nursing outcomes as many as 67 documents (64%). The conclusions in this study indicate that 67% of records have moderate quality on the dimensions of diagnosis as a process, 53% of documents have a reasonable condition on the aspects of diagnosis as a product, 63% of records have moderate quality on the dimensions of intervention, and 64% of documents have average quality on the dimensions of output nursing. The results of the nursing process that have been obtained in this study illustrate the change or improvement in the improvement of symptoms that have a moderate quality to integrate with the nursing process. Keywords: Diagnosis, Documentation, Intervention, Output